Soil organic carbon fractions are affected by different land uses in an agro-pastoral transitional zone in Northeastern China. (February 2017) - Yu, Pujia; Han, Kexin; Li, Qiang; Zhou, Daowei
Highlights: Land-use type had a significant effect on total SOC and SOC fractions. SOC was characterized by a predominantly very labile C fraction. Recalcitrant C fraction was less sensitive to land use and soil C changes. Grassland colonization improved soil C sequestration in northeastern China. Abstract: Soil organic carbon (SOC) consists of various C fractions with different stabilities and chemical compositions that are differently affected by changes in land use. A better understanding of the responses of different C fractions to land uses is vital for maintaining soil quality and mitigating global warming. Using data from a short-term land use experiment in northeastern China, this paper investigated the effect of five land uses, corn cropland (Corn), alfalfa grassland (Alfalfa), artificial grassland of Lyemus chinensis (AG), Lyemus chinensis grassland for mowing (AG + Mow) and restored grassland (RG), on the dynamics of total SOC and four SOC fractions with increasing degrees of oxidizability at 0 to 50 cm depths. The results show that land use had a significant effect ( P  < 0.05) on the total SOC and SOC fractions of very labile C (F1), labile C (F2) and less labile C (F3), while the difference in recalcitrant C (F4) was less pronounced. SOC in the study area was characterized by a predominantly very labile C fraction, and the percentages of F1 to total SOC were more than 40% for all land uses. Compared with Corn, the treatments AG + Mow, AG and RG decreased the percentage of F1 to SOC (by 4.49%, 6.53% and 3.55%, respectively) and increased the percentages of F2 (by 3.32%, 2.77% and 6.60%, respectively) and F3 (by 4.47%, 3.46% and 0.3%, respectively) to SOC. These findings suggest that land-use type is a major factor that influences soil C fractions and that labile C fractions contribute a large part of the total SOC. In addition, grassland colonization of croplands improves soil C sequestration in northeastern China.